Effect of internal sulfate attack on the properties of sulfate-resisting cement and alkali-activated slag. Issue 4 (4th July 2017) - Abdel Gawwad, H. A.; Abd El-Aleem, S.; Faried, A. S.
Abstract: This work aims at studying the effect of internal sulfate attack on the properties of sulfate-resisting cement (SRC) and alkali-activated slag (AAS). Blast-furnace slag was activated by 3% sodium hydroxide (NaOH) and 3% sodium silicate (Na2 SiO3 ) by weight of slag. Magnesium sulfate (MgSO4 ) solution with concentration of 0, 4, 12, and 20 wt.% was mixed with AAS and SRC at water to cement ratio (W/C) of .25. The results showed that the AAS setting times decrease with MgSO4 %. As the MgSO4 % increases up to 12%, the SRC setting times are elongated, and then shortened at 20%. The compressive strength of SRC decreases with the increase of MgSO4% . In contrast, the AAS compressive strength increases with MgSO4% up to 12%, then decreases at 20%. Drying shrinkage reduction and increment were observed when SRC and AAS were mixed with MgSO4 . These results were confirmed by X-ray diffraction, Fourier transformer infrared spectroscopy, and thermogravimetric (TG/DTG) analyses. The results proved that, the AAS can be beneficially used in cement concrete containing high sulfate concentration with better performance than SRC.